Problems of Reflecting Transactions with Digital Assets in Accounting - Andrii Makurin (Науковий вісник Мукачівського державного університету. Серія Економіка, 2020)
At the present stage of functioning of the digital economy, approaches to the use of cash are changing. Electronic non-cash payments are used to order services and pay for goods on the Internet increasingly often. Therefore, reflecting such operations in accounting constitutes an essential value for the accounting system. Using e-wallets and e-business environments, mapping cryptocurrency transactions, transferring funds, mining, investing in high-risk assets – all this requires learning the accounting methods for such transactions. The main purpose of this study is to scientifically substantiate approaches to reflecting operations with digital assets in accounting and determine the ways of receiving cryptocurrency by the enterprise. This study employed such methods of scientific cognition as description, analysis, and synthesis. It is established that there is no single approach to the recognition and accounting of cryptocurrencies. It is advisable to consider a cryptocurrency that belongs to intangible assets only in the context of long-term investments. Another development vector is identifying cryptocurrencies as a resource or inventory and accounting for them as inventory. It is determined that, first of all, before using cryptocurrencies, it is necessary to economically justify a certain method of evaluating cryptocurrencies legislatively. In the future, this will be necessary for companies that will use cryptocurrency to have the opportunity to continuously use this method in their accounting policies. The author of this study analysed the forms of electronic money and found that they can exist as information between computer networks (network-based) and can have an additional connection with a smart payment card (card-based). To identify the subject of accounting, the author determines that cryptocurrency should be considered as an intangible asset, while wallets for storing cryptocurrency should be considered as other non-current tangible assets